(untitled) (Al-Qamar, 2022)
Islam and humanity is a pivot to personal and collective life of human being. God has blessed him with remarkable gift of essence. Soul is not only a reflection of spiritual aura but also an intellectual aspect which furbish excellence in man. So that a man could prove himself a reasonable social being among the quagmire of oscillating being demands of society. These esoteric conditions flourish literature. Knowledge is a stimulus for intellect and reasoning in human being. Life is an eternal reality. Complete grasp of human nature is a herculean task. Literature elucidates the ideals of right and wrong as well as it depicts equality and brotherhood in peaceful society. The oneness of Allah, seal of prophets and anecdotes of saints are mentioned in a Masnavi “Mantiq Ul-Tair Jadeed” by Fareed-ud-Din Atar. Mustansar Hussain Tarrar, in his novel “Mantiq Ul-Tair Jadeed” has shed light upon philosophical, logical, metaphysical, ethical and psychological meanings of Islam and its harmony among interfaith on universal level. Historical religious and cultural values are metaphorically discussed in the perspective of worldy life and life after death. Above mentioned mystical discussions are presented in this article.